Development of chitosan based optical fiber chemical sensors - Ravikumar, Raghunandhan (2018)
In recent years there has been a tremendous progress in the development of polymer based fiber optic sensors. Particular emphasis on research has been focused on in-line fiber optic interferometric sensors owing to their many advantages like compact size, high sensitivity, immunity to electromagnetic interference etc. Among the polymers used in sensing applications, chitosan a natural biopolymer, has attracted a significant amount of interest. This thesis explores the possibilities of integrating chitosan with inline interferometric sensors for the sensing of chemical and biological species. The first work presented in the thesis involves an interferometric sensor with a no-core fiber (NCF) spliced between single mode fibers (SMF) and functionalized with chitosan (CS)/poly acrylic acid (PAA) self-assembled polyelectrolyte layers for the detection of heavy metal ion Nickel (II) (Ni2+). The sensing scheme is based on multi mode interference (MMI) i.e. interference of fundamental modes and excited higher order modes in the NCF, to detect changes in refractive index induced by Ni2+adsorption on the functionalized sensor. Wavelength shifts were measured real-time for the continuous monitoring of adsorption of Ni2+at different concentrations. The proposed sensor exhibits a linear response in the concentration range upto 500μM, with a Ni2+detection sensitivity of 0.0554 nm/ μM and concentration detection limit of 0.1671 μM. The second work presents an interferometric fiber sensor for detection of hexa-histidine tagged microcin (His-MccS). This intermodal fiber sensor is implemented by a no-core fiber (NCF) functionalized with chitosan (CS)-nickel (Ni) film for direct detection of small peptide: microcin. The fiber intermodal sensor relies on the refractive index modulations due to selective adsorption event at the chitosan (CS)-nickel (Ni) film. Owing to the strong affinity between Ni2+ ions and histidine, the immobilized Ni2+ ions in the chitosan film were utilized as binding agents for the direct detection of hexa-histidine tagged microcin. A comparative study in relation to different target size was conducted: full proteins trypsin, bovine serum albumin (BSA) and human serum albumin (HSA), with high histidine content on their surface and His-MccS (peptide, 11.6 KDa), have been employed for sensor evaluation. Results have shown selectivity for His-MccS relative to trypsin, BSA and HSA. The most telling contribution of this study is the fast detection of small biomolecule His-MccS compared to standard detection procedures like SDS-PAGE and western blot. The proposed sensor exhibits His-MccS detection sensitivity of 0.0308 nm/(ng/ml) in the range of (0-78) ng/ml with concentration detection limit of 0.8368 ng/ml. The third work involves an inline reflection mode intermodal sensor based on direct ligand immobilization for detection of nickel ions (Ni2+). Covalently immobilized nickel specific ligand, Meso-Tetra(4-carboxyphenyl)porphine, on the NCF surface serves as adsorption site for Ni2+ and can induce ambient refractive index (RI) change around the NCF on occurrence of binding events. The change in RI results in spectrum wavelength shifts, which was measured for continuous monitoring of Ni2+ concentration. The proposed sensor was observed to exhibit a sensitivity of 0.1210 nm/M towards Ni2+ ions. The final work demonstrates the use of molecularly imprinted chitosan functionalized PCF based MZI interferometric sensor for the detection of Ni2+ ions. The chitosan was crosslinked with epichlorohydrin (ECH) to increase its mechanical strength and thereby to improve the sensor stability. The sensor exhibits a Ni2+ detection sensitivity of 0.0604 nm/μM in the linear range and a limit of detection of 0.2008 μM. The sensor also shows a good specificity to Ni2+ ions compared to Cu2+, Ca2+, and Na+ ions. Investigation was carried out to examine the effect of crosslinking on the sensor performance by varying the ECH to chitosan molar ratio (5:1, 10:1, and 15:1). It is observed that the sensor achieved its best performance when the molar ratio was 10:1.